Komersialisasi Ruang Angkasa dan Tantangan Hukum Internasional: Analisis terhadap Privatisasi Eksplorasi Antariksa - Pramasya Findia Koes Wandari; Putri Hanny Virgilya; Dinno Afdhal Syaputra (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
The development of space commercialization, marked by increasing private sector involvement, has transformed the dynamics of international space law. This study aims to analyze international legal regulation and the legal responsibility of states and companies for damages arising from such activities. The research employs a normative legal method using statutory and conceptual approaches. The findings show that regulation still relies on the Outer Space Treaty 1967, which does not explicitly accommodate private actors, creating normative gaps. Liability remains dominated by the principle of state responsibility under the Liability Convention 1972, while private entities bear indirect responsibility. Therefore, adaptive legal reform is necessary to ensure legal certainty and justice.